A study of confirmation bias among online investors in virtual communities. (11th June 2021) - Trehan, Bhoomika; Sinha, Amit Kumar
The purpose of this study is to investigate the existence of confirmation bias among online investors participating in virtual communities. It further examines the factors such as perceived knowledge, investment experience, and gender that influence the confirmation bias. In the virtual communities, two types of participants were identified 'knowledge seekers' and 'knowledge contributors'. An online survey was conducted using structured questionnaire and the data was analysed with the application of relevant statistical tools. Investment-related virtual communities were found to be a great source of stock market-related news and investment ideas. The findings indicate that online investors exhibit confirmation bias as they join virtual communities to seek information that confirms their previous beliefs and opinions. The data was collected from online chat rooms where online investors interact and discuss investment trades. As many investors invest online without taking financial advice and guidance, their investment choices depend on their instinct and knowledge. Therefore, this study is of immense importance for both investors and investment advisors.